A method for synthesizing an aqueous photocurable resin and an article thereof

CN122897965APending Publication Date: 2026-10-13HUNAN CHIBANG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611381866.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

该方法通过特定的分子结构设计和反应路线规划,使树脂分子链上同时引入带羧基的含有可聚合双键的化合物的改性结构单元和具有能渗透溶胀塑胶基材并形成IPN结构的改性结构单元,旨在解决现有水性UV涂料对金属基材和各种塑胶基材附着力差的问题;水的高蒸发热(约40.6kj/mol)在预干燥步骤的耗能和费时问题,难以适应现有自动生产线的要求;水的高表面张力(72.8mN/m)引起的涂层表面缺陷的问题;水的凝固点高造成的配方复杂化问题;水性UV涂层镜面般的高光泽表面效果及涂层硬度与柔韧性的平衡问题,以符合3C电子产品的外观涂装要求

Benefits of technology

(1)独特的基材锚固机制--互穿网络(IPN)物理锚固:本发明创造性地引入了第二改性化合物,其均聚物对塑胶基材(如PC、ABS、PC/ABS等)具有优异的渗透溶胀能力。在涂覆与预干燥阶段,该组分能够渗透进入基材表层,在后续UV固化过程中,与涂层本体树脂在基材界面处形成一层很薄的互穿网络结构(IPN)。这种物理锚固方式不同于传统的化学键合,不依赖基材表面的活性官能团,因此具有极广泛的基材适应性--对表面惰性的塑胶基材均能实现优异的附着力。这一机制是本发明树脂“存在意义”的根本所在。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897965A_ABST
    Figure CN122897965A_ABST
Patent Text Reader

Abstract

The application discloses a synthesis method of water-based photocuring resin and an article thereof, and the core lies in a novel substrate adhesion enhancement mechanism. Two functional compounds are introduced in the synthesis process: a first compound containing a polymerizable double bond with a carboxyl group, which is used for providing water dispersibility of the resin and enhancing cohesion of the coating; and a second compound containing a polymerizable double bond, and a homopolymer of the second compound matches a solubility parameter of a plastic substrate, and the second compound invades a surface layer of the substrate by means of osmotic swelling, and a thin interpenetrating network structure (IPN) is formed at an interface between the coating and the substrate in a UV curing process, and physical anchoring different from traditional chemical bonding is realized. The anchoring mechanism is independent of active functional groups on the surface of the substrate, and excellent adhesion is achieved on various substrates such as inert plastic and metal, and the anchoring mechanism is a core basis for realizing practical performance of the resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer resin materials technology, specifically to a method for synthesizing a waterborne UV-curable resin, and waterborne UV-curable resin products prepared by this method, which can be widely used in the fields of coatings and inks. Background Technology

[0002] Photopolymerization technology has evolved into a new paradigm, moving from single-mechanism-driven to multi-mechanism coupling, marking a shift from parallel iteration to cross-integration in technological approaches. Photopolymerized aqueous systems, by simultaneously introducing photocurable and water-dispersible groups into the molecular chain, retain the low viscosity and easy-to-clean properties of aqueous systems while endowing the coating with photo-initiated rapid cross-linking capabilities, demonstrating significant advantages in coating complex workpieces and porous substrates. This organic integration of multi-functional group synergistic design and multi-stage curing mechanisms enables the coating to achieve non-linear superposition in dimensions such as cross-linking density, adhesion, and chemical resistance.

[0003] With increasingly stringent environmental regulations and ever-rising safety requirements in the coating industry, traditional solvent-based ultraviolet (UV) curing coatings, containing large amounts of volatile organic compounds (VOCs), pose serious fire safety hazards and environmental pollution problems even before curing, thus severely limiting their application. Water-based UV curing coatings, using water as the dispersion medium, can significantly reduce VOC emissions and eliminate fire hazards, and are considered a key development direction for next-generation green coating materials.

[0004] However, solvent-based UV coatings still dominate automated production lines in the computer, communication, and consumer electronics (hereinafter referred to as "3C electronics") sector. While water-based UV coatings offer significant environmental and safety advantages, their application in this field is severely limited due to numerous technical shortcomings in areas such as adhesion, resistance to corrosion, curing speed, and storage stability. These shortcomings make it difficult to meet the stringent appearance quality requirements of 3C electronics and the high-speed production cycles of automated coating lines.

[0005] Specifically, existing water-based UV coatings mainly suffer from the following technical problems: (1) Insufficient adhesion: There are many types of substrates for 3C electronic products, including plastics (PC, PC / ABS, nylon, etc.), metals, glass, etc. Existing water-based UV resins have poor universal adhesion to various substrates, and solvent-based primers are often used in addition, which deviates from the original intention of environmental protection.

[0006] (2) Poor resistance to media corrosion: The poor resistance of existing waterborne UV-curable coatings to media corrosion stems from three aspects: First, the hydrophilic groups such as carboxyl and sulfonic acid groups introduced to impart water dispersibility remain permanently after curing, forming osmotic pressure-driven active transport channels for water molecules; second, the contradiction between water dispersibility and curing density leads to a loose cross-linked network, allowing free volume cavities to directly allow corrosive media to penetrate the coating body; third, incompletely bonded film-forming aids and neutralizing agents remain as free small molecules, which dissolve in water and generate micropores in situ, further opening up the penetration pathways. Under high temperature and high humidity conditions, the medium rapidly penetrates into the coating-substrate interface along the above paths, destroying the adhesion anchor points and ultimately causing coating swelling, blistering, and peeling failure.

[0007] (3) Slow curing speed: Water has a high latent heat of vaporization. Water-based coatings need to be fully dried by water evaporation before UV curing, which prolongs the overall process time and makes it difficult to meet the efficiency requirements of automated production lines.

[0008] (4) Difficulty in balancing overall performance: The introduction of hydrophilic groups leads to a decrease in water resistance, while the reduction of hydrophilic groups leads to insufficient dispersion stability; increasing the degree of crosslinking improves hardness but sacrifices flexibility. Existing technologies struggle to achieve a good balance between adhesion, water resistance, curing speed, storage stability and coating mechanical properties.

[0009] Resin is the foundation of coatings. Therefore, developing a waterborne UV-curing resin with excellent adhesion, good water resistance, fast curing speed, and stable storage makes it possible to further expand waterborne UV coatings in the 3C electronics industry. This is of great significance for promoting the green transformation of the 3C electronic product coating industry and has broad market application prospects. Summary of the Invention

[0010] The purpose of this invention is to provide a waterborne UV-curable resin and its synthesis method. This method, through specific molecular structure design and reaction route planning, simultaneously introduces modified structural units containing polymerizable double bonds and carboxyl groups into the resin molecular chain, as well as modified structural units capable of penetrating and swelling plastic substrates to form an IPN structure. This aims to solve the problems of poor adhesion of existing waterborne UV coatings to metal and various plastic substrates; the energy consumption and time-consuming nature of water's high heat of vaporization (approximately 40.6 kJ / mol) in the pre-drying step, making it difficult to meet the requirements of existing automated production lines; the coating surface defects caused by water's high surface tension (72.8 mN / m); the formulation complexity caused by water's high freezing point; and the issues of achieving a mirror-like high-gloss surface effect and balancing coating hardness and flexibility in waterborne UV coatings, thus meeting the appearance coating requirements of 3C electronic products.

[0011] To achieve the above objectives, the present invention provides a method for synthesizing an aqueous photocurable resin, comprising the following steps: (1) Preparation of prepolymer: A macromolecular diol compound with a number average molecular weight in the range of 400 to 5000 and a polyol compound containing at least one hydrophilic group are mixed evenly in an inert polar aprotic solvent. A polyfunctional compound containing at least two isocyanate groups is added. The mixture is reacted at 30 to 85°C for 3 to 6 hours in the presence of a catalyst that promotes the reaction between isocyanate and hydroxyl groups to obtain a prepolymer with isocyanate group end capping. The system comprises 2% to 8% of the total mass of a macromolecular diol compound, 0.5% to 6% of the total mass of a polyol compound containing at least one hydrophilic group, preferably 1% to 4%; 3% to 8% of the total mass of a polyisocyanate compound; 0.02% to 0.06% of the total mass of a reaction catalyst; and 6% to 14% of an inert polar aprotic solvent (selected from at least one of N,N-dimethylacetamide and methyl ethyl ketone). (2) Functional monomer copolymerization: Add a first modifying compound and a second modifying compound to the prepolymer obtained in step (1), and continue the reaction at 60-85°C for 2-5 hours to obtain a functionalized modified prepolymer; wherein, the first modifying compound is an acrylate compound containing polymerizable double bonds with a carboxyl group, selected from at least one of methacrylic acid, acrylic acid, and β-carboxyethyl acrylate; the difference in solubility parameters between the homopolymer of the second modifying compound and the ABS / PC plastic substrate is... Its molecular structure contains polymerizable double bonds, which can produce a controllable penetration and swelling effect on the plastic substrate, forming a continuous interpenetrating polymer network (IPN) structure at the interface between the substrate and the coating. Specifically, it is selected from at least one of isobornyl methacrylate, isooctyl acrylate, and vinylpyrrolidone. (3) Photocurable functionalized end capping: Add a compound containing at least one (meth)acrylate group and at least one active hydrogen group that can react with isocyanate to the system obtained in step (2), and add a polymerization inhibitor. React at 50-80°C until the characteristic absorption peak of the isocyanate group completely disappears to obtain a photocurable resin prepolymer. (4) Neutralization and reverse emulsification: The prepolymer obtained in step (3) is cooled to 30-50°C, a neutralizing agent is added to adjust the pH to 7.0-8.5, deionized water is added under high-speed dispersion conditions to perform reverse emulsification, and then the organic solvent is removed to obtain an aqueous photocurable resin dispersion with a solid content of 30%-50%.

[0012] Preferably, in step (1), the macromolecular diol compound is selected from at least one of polyester diol, polyether diol, polybutadiene diol, and polycarbonate diol with a number average molecular weight of 400-5000; the hydrophilic group of the polyol compound containing hydrophilic groups is selected from at least one of carboxyl groups and sulfonic acid groups; and the catalyst that promotes the reaction between isocyanate and hydroxyl groups is selected from at least one of organic bismuth catalysts and tertiary amine catalysts.

[0013] Preferably, in step (2), the first modified compound is an acrylate compound containing a polymerizable double bond with a carboxyl group, selected from at least one of methacrylic acid, acrylic acid, and β-carboxyethyl acrylate, and the first modified compound accounts for 8% to 14% of the total mass of the system, more preferably 9% to 12%.

[0014] Preferably, in step (2), the difference in solubility parameters between the homopolymer of the second modified compound and the target ABS / PC plastic substrate is... Further optimization By matching the solubility parameters, the second modified compound is guaranteed to have controllable penetration and swelling ability on the plastic substrate, and can form a continuous interpenetrating network structure (IPN) in the interface area between the substrate and the coating during the coating curing process, thereby achieving the technical effect of physical anchoring to enhance adhesion.

[0015] More preferably, the second modified compound is selected from at least one of isobornyl methacrylate, isooctyl acrylate, and vinylpyrrolidone, and its molecule may also contain at least one reactive group selected from hydroxyl and phosphate ester groups; the reactive groups can form chemical bonds with the active sites on the substrate surface, realizing the synergistic effect of IPN physical anchoring and chemical bond adhesion, further improving the coating adhesion. The second modified compound accounts for 0.3% to 8% of the total mass of the system, preferably 0.5% to 5%.

[0016] The solubility parameters mentioned in this invention were all determined using the small molecule solvent dissolution method commonly used in the field of polymer materials. The testing environment was strictly controlled at a constant temperature of 25°C. The testing method was performed in accordance with the general testing specifications for polymer solubility parameters in the current valid national standards. The units of the final measured solubility parameter values ​​were uniformly set to [unit missing]. In this invention, "plastic substrate" specifically refers to any one of the three types of plastic substrates commonly used in the field of photocurable coating: acrylonitrile-butadiene-styrene copolymer (ABS), polyvinyl chloride (PVC), and polycarbonate (PC). These substrates are widely used in applications such as 3C electronic product casings, home appliance interior parts, and automotive trim, and are conventionally suitable substrates for photocurable coating operations by those skilled in the art. The "difference in solubility parameter between the homopolymer of the second modified compound and the plastic substrate" defined in this invention refers to the absolute difference between the solubility parameter value of the homopolymer of the second modified compound and the solubility parameter value of the corresponding suitable plastic substrate. The magnitude of this difference directly determines the molecular compatibility of the resin coating at the interface with the plastic substrate and is a core parameter for ensuring high coating adhesion.

[0017] To verify the effect of the solubility parameter difference range on coating adhesion performance in this invention, a control experiment was conducted under identical coating process conditions: second modified compounds with different solubility parameters were introduced into the waterborne UV-curable resin synthesis system to prepare corresponding resin samples. The resins were then formulated into a waterborne UV-curable coating with a solid content of 40%, and uniformly coated onto the surface of a PC plastic substrate by spraying. The solubility parameter range of the PC substrate was [missing information]. The coating thickness was controlled at 15μm. After pre-leveling at 60℃ for 5-6 minutes, a 395nm UV LED lamp was used at 800-900mJ / cm². 2 The irradiation energy was used to complete the photocuring. The coating adhesion was tested according to the GB / T 9286-1998 standard "Cross-cut test of paint and varnish films". The final control test results are as follows: 1. Control Group 1: The difference in solubility parameters between the homopolymer of the second modified compound and the PC substrate was [value missing]. After curing, the coating adhesion level in the cross-cut test was 3, and more than 15% of the coating in the cross-cut area peeled off, which could not meet the basic requirements for industrial coating.

[0018] 2. Example 1: The difference in solubility parameters between the second modified compound homopolymer and the PC substrate is: After curing, the coating adhesion level in the cross-cut test is Grade 1. Less than 5% of the coating edges in the cross-cut area show slight peeling. The overall coating adhesion is good and can meet the conventional coating requirements of ordinary plastic products.

[0019] 3. Example 2: The difference in solubility parameters between the second modified compound homopolymer and the PC substrate is: After curing, the coating adhesion level in the cross-cut test is 0, the cross-cut edges are completely smooth with no coating peeling, the coating and the substrate interface are tightly bonded, and the coating has excellent bending resistance. When it undergoes 5% deformation with the plastic substrate, there is no cracking or peeling problem, making it fully suitable for high-requirement coating scenarios such as 3C electronic products and automotive interior parts.

[0020] 4. Example 3: The difference in solubility parameters between the second modified compound homopolymer and the PC substrate is: After curing, the coating adhesion level in the cross-cut test is also 0. The coating interface forms a complete interpenetrating network structure. After 100 cycles of hot and cold cycling (-20℃~60℃), the adhesion still remains at 0, demonstrating excellent weather resistance and stability.

[0021] The above-mentioned results of multiple sets of comparative experiments fully demonstrate that when the difference in solubility parameters between the homopolymer of the second modified compound and the plastic substrate is significant... When this is achieved, a stable adhesion between the coating and the plastic substrate can be guaranteed; when the difference is further controlled within... When within the preferred range, the coating can achieve top-level adhesion performance with zero peeling, while also taking into account flexibility and weather resistance, completely solving the industry pain point of traditional water-based UV-cured coatings being prone to peeling and detachment on non-polar plastic substrates.

[0022] Preferably, in step (3), the polymerization inhibitor is selected from at least one of phenolic, quinone, and nitroxide radical polymerization inhibitors, and the amount used is 0.001% to 0.005% of the total mass of the system.

[0023] Preferably, in step (4), the neutralizing agent is selected from at least one of triethylamine, ammonia, N,N-dimethylethanolamine, 2-amino-2-methyl-1-propanol or sodium hydroxide.

[0024] The present invention also provides an aqueous photocurable resin prepared by any of the above-described synthesis methods.

[0025] The present invention also provides an aqueous photocurable coating composition comprising the above-described aqueous photocurable resin, a photoinitiator, an additive, and optionally water.

[0026] The present invention also provides a method and process for applying the above-mentioned waterborne UV-curable coating composition to the surface coating of 3C electronic product substrates.

[0027] Beneficial effects (1) Unique Substrate Anchoring Mechanism – Interpenetrating Network (IPN) Physical Anchoring: This invention creatively introduces a second modified compound, whose homopolymer exhibits excellent penetration and swelling capabilities on plastic substrates (such as PC, ABS, PC / ABS, etc.). During the coating and pre-drying stages, this component can penetrate into the substrate surface, and during the subsequent UV curing process, it forms a very thin interpenetrating network (IPN) structure with the coating bulk resin at the substrate interface. This physical anchoring method differs from traditional chemical bonding and does not rely on the active functional groups on the substrate surface, thus possessing extremely wide substrate adaptability – achieving excellent adhesion even to surface-inert plastic substrates. This mechanism is the fundamental reason for the "existence" of the resin in this invention.

[0028] (2) Excellent adhesion: During the synthesis process, the resin introduces a first compound containing a carboxyl group and polymerizable double bonds, and a second compound containing polymerizable double bonds whose homopolymer has the ability to penetrate and swell on plastic substrates and can form an interpenetrating network structure (IPN) between the substrate and the coating body. An anchoring functional groups that can form strong interactions with the substrate are embedded in the resin molecular structure, which significantly improves the adhesion of the coating to various substrates (plastic, metal, glass) of 3C electronic products.

[0029] (3) Excellent resistance to media corrosion: The waterborne UV coating prepared by the waterborne photocurable resin synthesized in this invention can form a highly cross-linked dense network structure after curing. The cross-linking degree of existing waterborne UV curing coatings is insufficient, with many small molecule residues, which are easily swollen and dissolved by the media; while the curing coating of this invention may only precipitate a small amount of residual small molecules that have not participated in cross-linking, and the gel rate of the curing coating can reach more than 90%, and the resistance to dissolution and swelling of dilute acids, dilute alkalis and common organic solvents is greatly improved.

[0030] (4) Fast curing speed: The resin molecular chain ends are densely covered with highly reactive (meth)acrylate double bonds, resulting in a fast photocuring rate; and the macromolecular structure design of the resin allows it to form a film quickly after the moisture evaporates, shortening the pre-drying time and perfectly meeting the requirements of automated production lines for 3C electronic products.

[0031] (5) Synergistic effect and performance balance: The two functional compounds used in this invention are not simply performance additions, but achieve synergistic effect at the molecular level. The first compound with carboxyl groups provides stable water dispersibility and intermolecular hydrogen bonding, and also has the effect of enhancing cohesion. The second compound, which can penetrate to form an IPN structure, achieves excellent substrate anchoring through interfacial interpenetration. The two compounds work together to give the coating excellent substrate adhesion and interlayer bonding, while also helping to improve the mirror leveling effect of the coating. Finally, the gloss, fullness, brightness, hardness, wear resistance, scratch resistance and thermal stability of the coating can basically reach the performance level of solvent-based UV coatings, achieving a balance between water-based and high performance.

[0032] (6) Excellent mirror leveling effect: While providing a high gloss surface effect, it also takes into account the balance between coating hardness and flexibility in order to meet the appearance coating requirements of 3C electronic products. Attached Figure Description

[0033] Figure 1 This is a process flow diagram of the waterborne photocurable resin synthesis method of the present invention. Detailed Implementation

[0034] The following provides the general operating steps of the waterborne photocurable resin synthesis method of the present invention. It should be noted that the following steps describe the general technical solution of the present invention, wherein all materials used are described using higher-level concepts; specific material selection and parameter optimization will be detailed in subsequent embodiments.

[0035] Step 1: Raw material preparation and pretreatment Step 1: Add macromolecular diol compounds with a number average molecular weight in the range of 400 to 5000 to the reaction vessel, and dehydrate under reduced pressure at 90 to 110°C and a vacuum degree of -0.09 to -0.1 MPa for 1 to 2 hours until the water content is ≤500 ppm. Cool to room temperature to 60°C.

[0036] Step 2: Add a polyol compound containing at least one hydrophilic group to the dehydrated macromolecular diol. The hydrophilic group is selected from at least one of carboxyl or sulfonic acid groups. The amount of the hydrophilic group is 1% to 15% of the total mass of the macromolecular diol in Step 1 and the hydrophilic polyol in this step, preferably 3% to 10%.

[0037] Step 3: Add sufficient inert polar aprotic solvent and stir at room temperature to 60°C until the system is completely dissolved and in a transparent homogeneous state to obtain a mixed diol solution.

[0038] Step 4: Keep the system temperature at 30-60°C, and add a polyfunctional compound containing at least two isocyanate groups. The amount of the polyfunctional compound added is 1.2-2.5 based on the NCO / OH molar ratio.

[0039] Step 5: Add a catalyst to promote the reaction between isocyanate and hydroxyl groups, in an amount of 0.01% to 0.5% of the total solid content of the system.

[0040] Step 2: Prepolymer reaction Step 6: Under a nitrogen protective atmosphere, heat the system to 50-80°C and stir the reaction for 3-6 hours.

[0041] Step 7: Monitor the change in the content of isocyanate groups in the system during the reaction. When the NCO content drops to within ±5% of the theoretical residual value, the prepolymerization reaction is determined to have reached its endpoint, and the NCO-terminated prepolymer is obtained.

[0042] Step 3: Functional monomer copolymerization Step 8: While maintaining the NCO-terminated prepolymer system at 60–85°C, add a first modifying compound. The first modifying compound is an acrylate compound containing polymerizable double bonds and a carboxyl group, selected from at least one of methacrylic acid, acrylic acid, and β-carboxyethyl acrylate. The carboxyl group provides the hydrophilicity required for water dispersion after subsequent neutralization and salt formation, and also participates in intermolecular hydrogen bonding, enhancing the coating's cohesiveness. The amount of this first modifying compound is 5%–15% of the total mass of the system, preferably 8%–14%.

[0043] Step 9: Add a second modifying compound, the difference in solubility parameters between the homopolymer of this second modifying compound and the target plastic substrates such as PC and ABS. Further optimization Its molecular structure contains polymerizable double bonds, enabling it to exert controllable penetration and swelling on the plastic substrate, and to form a continuous interpenetrating network (IPN) structure at the interface between the substrate and the coating. Preferably, the second modified compound is selected from at least one of isobornyl methacrylate, isooctyl acrylate, and vinylpyrrolidone, and its homopolymer solubility parameter is similar to that of the PC substrate (approximately...). The second modified compound is highly compatible. Its dosage is 0.3%–8% of the total solid content of the system, preferably 0.5%–5%.

[0044] Step 10: Under a nitrogen protective atmosphere, stir the reaction at 60-85℃ for 2-5 hours to obtain the functionalized modified prepolymer.

[0045] Step 11: Sample and detect further changes in double bond conversion rate or NCO content in the system to confirm that the functional monomer has fully participated in the reaction.

[0046] Step 4: Photocurable functionalized end capping Step 12: Set the reaction temperature of the functionalized modified prepolymer to 50–80°C.

[0047] Step 13: Add a compound containing at least one (meth)acrylate group and at least one active hydrogen group that can react with isocyanate as a capping agent, in an amount of 0.8 to 1.2 times the number of moles of residual NCO in the system.

[0048] Step 14: Add a polymerization inhibitor at a rate of 0.001% to 0.005% of the total solid content of the system. The polymerization inhibitor can be selected from at least one of phenolic, quinone, and nitroxide free radical polymerization inhibitors.

[0049] Step 15: Stir the reaction for 2 to 4 hours under a nitrogen protective atmosphere at 60–75°C.

[0050] Step 16: Use Fourier transform infrared spectroscopy (FTIR) to monitor the characteristic absorption peak of the isocyanate group in the system (approximately 2270 cm⁻¹). -1 The intensity change of the characteristic absorption peak is observed. If the characteristic absorption peak disappears completely, the end-capping reaction is considered complete; if there is a residual peak, an appropriate amount of end-capping agent is added and the reaction continues for 0.5 to 1 hour until the characteristic absorption peak disappears completely. A photocurable resin prepolymer is obtained.

[0051] Step 5: Neutralization and Conversion Emulsification Step 17: Cool the photocurable resin prepolymer to 30-50°C.

[0052] Step 18: Add a neutralizing agent to adjust the pH of the system to 7.0–8.5. The neutralizing agent can be at least one of triethylamine, ammonia, N,N-dimethylethanolamine, 2-amino-2-methyl-1-propanol, or sodium hydroxide. Stir for 10–30 minutes until the neutralization reaction is complete.

[0053] Step 19: Prepare deionized water at a temperature of 25-40℃. The total amount used is calculated based on the final product solid content of 30%-50%.

[0054] Step 20: Under high-speed dispersion conditions (stirring speed 600-1200 rpm), slowly add deionized water to the system dropwise or in a thin stream to perform reverse emulsification.

[0055] Step 21: Sample and test the average particle size and particle size distribution of the dispersion. The average particle size should be controlled between 50 and 300 nm, and the particle size distribution index (PDI) should be ≤0.3.

[0056] Step Six: Solvent Removal and Finished Product Discharge Step 22: Remove the organic solvent from the system by vacuum distillation at a temperature of 40–60℃ and a vacuum degree of -0.08–-0.1 MPa. The removed organic solvent can be recycled after condensation.

[0057] Step 23: Take a sample to test the solid content and adjust it to 30%–50%. Filter the sample through a filter screen or filter cartridge with a pore size of 5–50 μm to obtain the finished water-based photocurable resin dispersion.

[0058] Example 1

[0059] Using the same procedures as the "General Steps of Synthesis Method" described above, the specific raw materials and process parameters used in this embodiment are as follows: Step 1: The macromolecular diol compound is polyester diol A (number average molecular weight 1000, [code: POL-1]), and the amount used is 80g.

[0060] Step 2: The polyol compound containing hydrophilic groups is a carboxyl-containing polyol (

code: W-Monomer-1

[0061] Step 3: The inert polar aprotic solvent is N,N-dimethylacetamide (DMAC), 30g.

[0062] Step 4: The polyfunctional isocyanate compound is isophorone diisocyanate (IPDI) with an NCO / OH molar ratio of 1.8.

[0063] Step 5: An organic bismuth catalyst is selected, with a dosage of 0.05g.

[0064] Steps 6-7: Prepolymerization reaction temperature 70℃, reaction time 3 hours, stirring speed 300rpm.

[0065] Step 8: The first modifying monomer is a carboxyl-containing acrylate monomer (code: M1-COOH), specifically methacrylic acid (MAA), with an amount of 7.2g (approximately 10% of the total mass of the system).

[0066] Step 9: The second modifying monomer is a monomer with the ability to penetrate and swell in plastic substrates (code: M2-IPN), specifically isobornyl methacrylate (IBOMA), whose homopolymer has a solubility parameter difference with the PC substrate. It can form a continuous IPN interpenetrating network structure at the coating / substrate interface, with a dosage of 3.6g (accounting for approximately 3% of the total solid content of the system).

[0067] Steps 10-11: Functional monomer copolymerization reaction temperature 75℃, reaction time 2 hours.

[0068] Steps 12-16: The capping agent is hydroxyethyl acrylate (HEA), with a dosage of 26g; the polymerization inhibitor is p-methoxyphenol (MEHQ), with a dosage of 0.003g; the capping reaction temperature is 60℃, and the reaction time is 3 hours.

[0069] Steps 17-18: Use 2-amino-2-methyl-1-propanol (AMP) as the neutralizing agent and adjust the pH to 7-8.

[0070] Steps 19-21: Conversely, emulsify at 800 rpm, and calculate the amount of deionized water to achieve a final solid content of 35%.

[0071] Steps 22-23: After removing the solvent by vacuum distillation, adjust the solid content to 35%, filter to obtain an aqueous photocurable resin dispersion, labeled as E1.

[0072] The average particle size of E1 was measured to be 118 nm, and the PDI was 0.15.

[0073] Example 2

[0074] This embodiment is essentially the same as Example 1, except that: in step 1, polyester diol A (POL-1) is replaced with polybutadiene diol B (number average molecular weight 2000, [code: POL-2]), with the amount remaining at 80g; and the amount of carboxyl-containing polyol (W-Monomer-1) is adjusted to 3.5g (approximately 4.2% of the total polyol mass) to investigate the effect of different macromolecular diols on the water resistance and flexibility of the coating film. The resulting resin is labeled E2.

[0075] The average particle size of E2 was measured to be 135 nm, and the PDI was 0.18.

[0076] Example 3

[0077] This embodiment is basically the same as Example 1, except that the carboxyl-containing polyol (W-Monomer-1) in step 2 is replaced with a polyol containing sulfonic acid groups (

code: W-Monomer-2

[0078] The average particle size of E3 was measured to be 105 nm, and the PDI was 0.13.

[0079] Comparative Example 1 This comparative example is used to examine the synergistic effect of two functionally modified monomers.

[0080] The preparation method is basically the same as in Example 1, except that steps 8 and 9 are completely omitted, i.e., the first modified monomer (M1) and the second modified monomer (M2) are not added, and the subsequent end-capping and emulsification processes are carried out directly. The resulting resin is labeled C1.

[0081] The average particle size of C1 was measured to be 125 nm, and the PDI was 0.20.

[0082] Comparative Example 2 This comparative example is used to examine the differences between macromolecular diols and low-molecular-weight diols.

[0083] The preparation method is basically the same as in Example 1, except that the polyester diol A (POL-1) in step 1 is completely replaced with an equimolar amount of the small molecule diol 1,4-butanediol (BDO, number average molecular weight 90), while the other conditions remain unchanged. The resulting resin is labeled C2.

[0084] The average particle size of C2 was measured to be 160 nm, and the PDI was 0.25.

[0085] 5.2 Performance Testing: (1) Preparation of waterborne UV coatings: The waterborne UV-curing resins obtained in the above examples and comparative examples are mixed with the same amount of photoinitiator (Darocur1173, 3wt%), appropriate amount of additives and deionized water, and stirred thoroughly to prepare waterborne UV-curing coatings.

[0086] (2) Pretreatment of substrates: The transparent PC, black ABS, white ABS plastic substrates and metal substrates (tinplate) are pretreated respectively: the plastic substrates are degreased and dusted; the metal substrates (tinplate) are polished, wiped with solvent to remove oil and rust, and dusted to ensure that the surface is clean and dry in order to obtain good coating adhesion.

[0087] (3) Fabrication of the test board Clean the surfaces of the substrates after the pretreatment in step (2), and directly spray the water-based UV coating prepared in step (1). The resulting coating thickness is approximately 20 μm. After pre-drying at 60°C for 5-8 minutes, cure the coating in a UV curing machine at 600-800 mJ / cm². 2 The energy is used to cure the UV light, thus obtaining each test plate.

[0088] Fabrication of RCA Paper Tape Abrasion Resistance Test Plate In the water-based UV coating prepared in step (1), add an additional 2% (mass fraction) of water-based black pigment and stir evenly; perform substrate pretreatment according to step (2), prepare test board according to the spraying and curing process in step (3), control the dry film thickness of the coating to 13μm, and obtain RCA paper tape abrasion resistance test board.

[0089] Table 1: Comparison of adhesion performance between coatings and substrates in various examples and comparative examples (Adhesion test method: 5 cross-cut tests with 3M tape).

[0090] Table 2: Comparison of coating performance between each embodiment and the comparative example

[0091] 5.3 Results Analysis: As can be seen from the table above: (1) Synergistic effect of functional monomers (E1 vs C1): Example E1 is significantly better than comparative example C1 in terms of adhesion (5B vs 0B), water resistance (no change vs severe whitening and blistering), ethanol wiping resistance, flexibility and impact resistance. This fully demonstrates that there is a significant synergistic effect between the first modified compound and the second modified compound - the carboxyl-containing polymerizable double bond compound A and the compound B that can penetrate and swell plastic substrates to form IPN structures do not act independently, but through the synergistic arrangement on the molecular chain, they simultaneously achieve high crosslinking density and efficient interface anchoring of the coating film after photocuring, and the comprehensive performance is far greater than the simple sum of the two.

[0092] (2) The irreplaceability of macromolecular diols (E1 vs C2): In comparative example C2, after replacing the macromolecular diol with small-molecule BDO, the coating flexibility decreased sharply (>5mm cracking) and the impact resistance was extremely poor (<10cm·kg), indicating that the molecular chain flexibility provided by the macromolecular diol is the key to the good mechanical properties of the resin of this invention. This performance difference is essential and not within the scope that a person skilled in the art could reasonably foresee in advance.

[0093] Those skilled in the art will understand that the core contribution of this invention lies in proposing an adhesion-enhancing mechanism that "achieves substrate penetration and swelling through solubility parameter matching, forming an interpenetrating network (IPN) structure at the coating-substrate interface." Based on this concept disclosed in this invention, those skilled in the art can, without creative effort, select other compounds with similar solubility parameters and penetration capabilities to replace the preferred second compound disclosed in the specific embodiments of this invention. Such simple substitutions do not change the technical principles of this invention and can still achieve the inventive purpose and substantially the same technical effects. Therefore, such equivalent substitutions and simple modifications all fall within the protection scope of this invention.

Claims

1. A method for synthesizing an aqueous photocurable resin, characterized in that, Includes the following steps: (1) A macromolecular diol compound with a number average molecular weight in the range of 400 to 5000 and a polyol compound containing at least one hydrophilic group are mixed evenly in an inert polar aprotic solvent. A polyfunctional compound containing at least two isocyanate groups is added. The mixture is reacted at 30 to 85°C for 3 to 6 hours in the presence of a catalyst that promotes the reaction between isocyanate and hydroxyl groups to obtain a prepolymer with isocyanate group end caps. The polyol compound containing at least one hydrophilic group accounts for 1% to 15% of the total mass of the macromolecular diol compound and the hydrophilic polyol compound. (2) Add the first modified compound and the second modified compound to the prepolymer obtained in step (1), and continue to react at 60-85°C for 2-5 hours to obtain the functionalized modified prepolymer; The first modified compound is an acrylate compound containing a carboxyl group and a polymerizable double bond, selected from at least one of methacrylic acid, acrylic acid, and β-carboxyethyl acrylate; The difference in solubility parameters between the homopolymer of the second modified compound and the plastic substrate Its molecular structure contains polymerizable double bonds, which can penetrate and swell the plastic substrate, forming an interpenetrating network (IPN) between the substrate and the coating. Specifically, it is selected from at least one of isobornyl methacrylate, isooctyl acrylate, and vinylpyrrolidone. (3) Add a compound containing at least one (meth)acrylate group and at least one active hydrogen group that can react with isocyanate to the system obtained in step (2), and add a polymerization inhibitor. React at 50-80°C until the characteristic absorption peak of the isocyanate group completely disappears to obtain a photocurable resin prepolymer. (4) Cool the prepolymer obtained in step (3) to 30-50°C, add a neutralizing agent to adjust the pH to 7.0-8.5, add deionized water under high-speed dispersion conditions to perform reverse emulsification, and then remove the organic solvent to obtain an aqueous photocurable resin dispersion with a solid content of 30%-50%.

2. The synthesis method according to claim 1, characterized in that, In step (2), the difference in solubility parameters between the homopolymer of the second modified compound and the plastic substrate... .

3. The synthesis method according to claim 1, characterized in that, In step (1), the polyol compound containing at least one hydrophilic group accounts for 3% to 10% of the total mass of the macromolecular diol compound and the hydrophilic polyol compound.

4. The synthesis method according to claim 1, characterized in that, In step (1), the macromolecular diol compound is selected from at least one of polyester diol, polyether diol, polybutadiene diol, and polycarbonate diol.

5. The synthesis method according to claim 1, characterized in that, In step (1), the hydrophilic group is selected from at least one of carboxyl group and sulfonic acid group.

6. The synthesis method according to claim 1, characterized in that, In step (2), the functional group of the first modified compound is selected from at least one of fluorinated substituents, long-chain alkyl groups, cycloalkyl groups, and aromatic groups.

7. The synthesis method according to claim 6, characterized in that, The functional groups of the first modified compound are fluorinated substituents or long-chain alkyl groups.

8. The synthesis method according to claim 1, characterized in that, In step (2), the functional group of the second modified compound is selected from at least one of hydroxyl, epoxy, amino, silanoxy, and phosphate groups.

9. The synthesis method according to claim 8, characterized in that, The functional group of the second modified compound is a hydroxyl or an epoxy group.

10. The synthesis method according to claim 1, characterized in that, In step (2), the first modified compound accounts for 9% to 12% of the total mass of the system; the second modified compound accounts for 0.5% to 5% of the total mass of the system.

11. The synthesis method according to claim 1, characterized in that, In step (1), the catalyst that promotes the reaction between isocyanate and hydroxyl group is selected from at least one of organotin, organobismuth, and tertiary amine catalysts.

12. The synthesis method according to claim 1, characterized in that, In step (3), the polymerization inhibitor is selected from at least one of phenols, quinones, and nitroxide radical polymerization inhibitors; in step (4), the neutralizing agent is selected from at least one of triethylamine, ammonia, N,N-dimethylethanolamine, 2-amino-2-methyl-1-propanol, or sodium hydroxide.

13. A water-based photocurable resin, characterized in that, It is prepared by the synthesis method according to any one of claims 1 to 11.

14. A component of a water-based UV-curable coating, characterized in that, By weight, it comprises 30-65 parts of the aqueous photocurable resin as described in claim 13, 1-5 parts of photoinitiator, 0.5-8 parts of additives, and the balance being deionized water.

15. The waterborne UV-curable coating composition according to claim 14, characterized in that, Application of this coating composition in surface coating of 3C electronic product substrates.